Pengaruh Kompetensi Aparatur, Komitmen Organisasi, Dan Partisipasi Masyarakat Terhadap Akuntabilitas Pengelolaan Dana Desa Di Kecamatan Batujajar - Madhalena Giriani; Neneng Dahtiah; Dian Imanina Burhany (Indonesian Accounting Research Journal, 2021)
The distribution of the village fund budget, which increases every year requires accountability for village fund management to the village government in Batujajar District. In this case, to produce accountability for good village fund management, the village government in Batujajar District needs to improve competence, organizational commitment, and community participation. This research aims to determine the effect of apparatus competence, organizational commitment, and community participation on the accountability of village fund management partially and simultaneously. This research uses a purposive sampling approach with a total of 112 respondents. The results of this research indicate that partially the competence of the apparatus has a positive and significant effect on the accountability of village fund management. Meanwhile, partially organizational commitment and community participation have a positive effect but not significant on the accountability of village fund management. In addition, apparatus competence, organizational commitment, and community participation have a positive and significant effect on the accountability of village fund management simultaneously.